Development of one-year major adverse cardiac events risk index in patients with acute coronary syndrome and diabetes mellitus who underwent percutaneous coronary intervention - Mirković, Marija Radivoje; Nedeljković, Milan; Ružičić, Dušan; Vuković, Mira (Vojnosanitetski pregled, 2020)
Background/Aim.  Patients with acute coronary syndrome (ACS) and diabetes mellitus (DM) have an increased risk of major adverse cardiovascular events (MACE) after percutaneous coronary intervention (PCI), which is not estimated sufficiently-multidimensionally in terms of type and severity of the ACS and/or DM and angiographic findings. The study was intended to validate and develop an index of metabolic, angiographic, anatomic and clinical risk factors for one-year MACE after conducted PCI in patients with ACS and DM. Methods. A prospective cross-sectional study was performed in patients with DM and ACS. In the PCI period the following risk factors were recorded: 1) age and metabolic variables – glycosylated hemoglobin (HbA1c), total cholesterol, and triglycerides levels in the blood; 2) endocrinological variables – DM therapy and type of DM; 3) ACS modality; 4) radiological/anatomical variable – SYNTAX score, and 5) clinical variables in modified age, creatinine, ejection fraction (ACEF) score.  One-year MACE were recorded. Results. From a total of 136 consecutive patients, 55 of them developed at least one MACE in one-year follow-up. A high predictive risk index was evaluated that assessed particular or associated risks for one-year MACE (c statistic = 0.879) in the study population, defined by: SYNTAX score > 21, modified ACEF score > 1.38, HbA1c ≥ 8%, triglyceridemia ≥ 2.3 mmol/L in patients with insulin therapy, and ACS modality – unstable angina pectoris. The constructed risk index for one-year MACE (MACERI) had better predictive characteristics than SYNTAX score (c statistic = 0.798), as well as ACF score (c statistic = 0.744). Conclusion. MACERI can potentially have great application in future risk factors studies for one-year MACE in patients with DM and ACS who underwent PCI, because with it the effects of these factors are measured multidimensionally at valid and accurate manner.
Keywords: coronary artery disease; coronary angiography; dia-betes mellitus; comorbidity; cardiovascular diseases; acute disease; risk factors